Essential Drivers of Customer Satisfaction in using Shopee Apps: A Perspective of Logistic Service Dimensions - Tedjakusuma, Adi Prasetyo; Harly, Kevin Richard; Andajani, Erna (Journal of Business & Banking, 2023)
This study was motivated by authors’ curiosity to study Shoppe as a booming e-commercecompany, while logistics services are critical for Shopee’s success in term of satisfyingits customers. This study aims to examine how factors of logistic dimensions affectcustomer satisfaction of Shoppe and is basic research. The authors applied a correlationalresearch type with a quantitative approach. The primary data were obtained directly fromrespondents by distributing a questionnaire. They were analyzed using SEM approachand Analysis of Moment Structures (AMOS) software. The results show that of 7hypotheses are supported. All factors of logistics dimensions: availability, delivery time,shipping cost, delivery reliability, product quality and condition, consumer complaintand return policy, and information quality affect customer satisfaction. This implies thatShoppe must make its stocks available, ensure its delivery time on time, pay attentionon its shipping cost, ensure the delivery of goods is in accordance with the conditionsapplied, the product packaging during shipping is not damaged, a simple return policy,provide information that meets expectations to satisfy its consumers. The present studycan shed light on the logistics services dimensions that align with customer expectationsin the e-commerce industry. Understanding these crucial logistics dimensions can enableShopee to better tailor their logistics operations to meet and exceed customer needs,ultimately resulting in satisfaction.